Advanced musculoskeletal physiotherapy practice: The patient journey and experience. (February 2020) - Fennelly, Orna; Blake, Catherine; FitzGerald, Oliver; Caffrey, Aoife; Fletcher, Laura; Smart, Keith; Corcoran, Siobhan; Shé, Éidín Ní; Casserley-Feeney, Sarah; Desmeules, François; Cunningham, Caitriona
Abstract: Background: As many patients referred to orthopaedic and rheumatology services do not require medical or surgical interventions, advanced practice physiotherapists (APPs) have been introduced into hospital services to triage the care of these patients. Patient perspectives are critical to review the acceptance of this model of care and potential for expansion into primary care. This study aimed to explore the clinical journeys, and the experiences and perceptions of patients attending APP services. Method: Semi-structured interviews (n = 10) were conducted with patients across two hospital sites, with narrative data subjected to a thematic analysis. MSK journeys were mapped via medical chart and interview data, with surveys collecting demographics. Results: Patient journeys involved multiple contact points and some duplication in MSK health services. Overall, experiences of the APP service were positive, with faster access into the hospital system and patients valued the interpersonal and professional skills of the APP. Having already attended a physiotherapist, some patients did have a preconception of what the APP could offer them. However, initial concerns were mitigated following the APP appointment, as the APP had extensive MSK knowledge. Hospitals remained the preferred location for MSK appointments due to availability of diagnostics and 'specialists', and close proximity of the doctor. Conclusion: Patients were positive about the new MSK APP service and benefits related to shorter wait times and seeing a specialist who listened and involved them in their management. However, a cultural shift regarding patient perceptions of the 'specialists' in hospitals and the role of a physiotherapist is required. Highlights: Positive experiences and reduced wait times were reported by patients. Patients valued the interpersonal skills and MSK knowledge of the APPs. Hospitals were the preferred location by patients for the MSK appointment. Duplication in health services occurred throughout the patient journey.